Digital Transformation as a Moderator in the Relationship between Green Entrepreneurial Orientation and Financial Bootstrapping on Financial Performance - Yogatama, Ahmad Nizar; Sudarmiatin; Wening Patmi Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines how digital transformation can moderate the relationship between Green Entrepreneurial Orientation (GEO) and Financial Bootstrapping on the financial performance of culinary Micro, Small, and Medium Enterprises (MSMEs) in Malang City. Data was collected from 390 MSMEs in the food and beverage industry using questionnaires and analyzed using multiple linear regression and moderated regression analysis. This regression model highlights the significance of Green Entrepreneurial Orientation and Financial Bootstrapping as primary methods influencing the financial success of MSMEs. Digital Transformation as moderated is significant. To get best outcomes, MSMEs must integrate sustainability methods with financial efficiency concurrently, rather than concentrating on a singular aspect.